2008
DOI: 10.5194/cp-4-147-2008
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in early spring wind regime in North-East Europe (1955–2007)

Abstract: Abstract. Changes to the winter-to-spring switch-time of the upper air flow regime at the 850 and 500 hPa levels over the north-eastern Baltic Sea are analyzed based on a data set extending from 1955 to 2007. The long-term variation of the air flow in early spring (March) exhibits multiple regime shifts. The shifts are extracted by means of a vector analysis of the monthly mean air flow and using statistical shift detection technology. In the middle of the 1960s the average air flow turned from NW (WNW) to W (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…The shift year 1989 was found for the majority of time series analysed in this study. This result is in good concordance with the previous investigations in the same region (Keevallik and Soomere, 2008;Elken et al, 2014;Soomere et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The shift year 1989 was found for the majority of time series analysed in this study. This result is in good concordance with the previous investigations in the same region (Keevallik and Soomere, 2008;Elken et al, 2014;Soomere et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…An increase in zonal circulation starting in 1987 was detected in February (Keevallik and Soomere, 2008). A similar shift at the end of the 1980s was found in the time series of cumulative wind stress calculated for December-January using data from Utö (Elken et al, 2014).…”
Section: Introductionmentioning
confidence: 52%
“…8b). Keevallik & Soomere (2008) observed a shift in the early-spring wind regime over the northeastern Baltic area. They concluded that multiple regime shifts in the wind components happened between different periods (PKS1: 1955-1966, PKS2: 1967-1995, PKS3: 1996, especially pronounced in March.…”
Section: Regional Atmospheric Variabilitymentioning
confidence: 92%
“…Comparable shifts for early spring were also reported for Finland by Keevallik and Soomere (2008) and Keevallik (2011) from the 1960s to 1990s with changes to more westerly than north-westerly winds. For the period 1966-2011, Jaagus and Kull (2011) also found a clear change in the main wind direction over Estonia in winter changing from south-east in the 1970s to south-west in the last decade.…”
Section: Wind Climate In Recent Decadesmentioning
confidence: 61%